2015
DOI: 10.1089/scd.2014.0488
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-MSCs Combined with Low-Dose Rapamycin Induced Islet Allograft Tolerance Through Suppressing Th1 and Enhancing Regulatory T-Cell Differentiation

Abstract: Mesenchymal stem cell (MSC) differentiation is dramatically reduced after long-term in vitro culture, which limits their application. MSCs derived from induced pluripotent stem cells (iPSCs-MSCs) represent a novel source of MSCs. In this study, we investigated the therapeutic effect of iPSC-MSCs on diabetic mice. Streptozocin-induced diabetic mice transplanted with 400 islets alone or with 1 · 10 6 iPSC-MSCs were examined following rapamycin injection (0.1 mg/kg/day, i.p., from days 0 to 9) after transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 69 publications
2
26
0
Order By: Relevance
“…While derivation of ESC‐MSCs was first reported in 2005 and demonstration of immunomodulation has been consistent for this type of PSC‐derived MSCs , studies on iPSC‐MSC immunomodulation have been few and discrepant. The most consistent immunomodulatory findings for iPSC‐MSCs are found in in vivo disease model studies, which demonstrate that these MSCs modulate CD4 T cells toward a Treg phenotype; however, effects on IFN‐γ, a cytokine representing effector Th1, was inconsistent and dependent on the disease model used . In vitro studies showed even less consistent results, with one study demonstrating strong immunomodulation toward natural killer lymphocytes whereas another study did not find any immunomodulatory effects .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…While derivation of ESC‐MSCs was first reported in 2005 and demonstration of immunomodulation has been consistent for this type of PSC‐derived MSCs , studies on iPSC‐MSC immunomodulation have been few and discrepant. The most consistent immunomodulatory findings for iPSC‐MSCs are found in in vivo disease model studies, which demonstrate that these MSCs modulate CD4 T cells toward a Treg phenotype; however, effects on IFN‐γ, a cytokine representing effector Th1, was inconsistent and dependent on the disease model used . In vitro studies showed even less consistent results, with one study demonstrating strong immunomodulation toward natural killer lymphocytes whereas another study did not find any immunomodulatory effects .…”
Section: Discussionmentioning
confidence: 81%
“…MSCs derived from human ESCs (ESC‐MSCs) were the first to be reported on, and with the exception of one study in which only one cell line was used , nearly all studies have found significant immunomodulatory effects for these MSCs . On the other hand, data on iPSC‐MSC immunomodulation have ranged from immunosuppression to no effect , to immunoreactive . Unlike ESCs, iPSCs can be artificially generated from any somatic cell sources using many methods, but cell‐of‐origin differences can result in alterations in differentiation capacity .…”
Section: Introductionmentioning
confidence: 99%
“…We previously differentiated iPSCs to MSCs and reported that iPSC‐MSCs, when compared to BM‐MSCs, showed a similar phenotype but longer life span . Transplantation of iPSC‐MSCs not only inhibited both CD4 and CD8 positive T cell subsets , but also expressed less HLA‐II under IFN‐γ stimulation . MSCs isolated from diverse human iPS cell lines can strongly inhibit the cytotoxic functions of NK cells and T helper 2 (Th2) cells mediated allergy .…”
Section: Introductionmentioning
confidence: 99%
“…1 In concordant models, such as the mouse-to-rat heart transplantation model, the organs undergo cell-mediated rejection when the acute humoral xenograft rejection (AHXR), also known as DXR, is suppressed by sustained treatment with a B-lymphocyte inhibitor. 2 AHXR occurs within 3 days after transplantation in the mouse-to-rat and hamster-to-rat heart transplantation models, characterized by binding of different immunoglobulins (Ig) to the vascular endothelium, vasculitis, thrombosis, tissue destruction, and edema. 3 Turnquist et al 4 observed a potent ability of interleukin (IL)-33 to increase suppressive CD4 + Foxp3 + regulatory T cells (Tregs).…”
mentioning
confidence: 99%